Newborn care knowledge and practices among care givers of newborns and young infants attending a regional referral hospital in Southwestern Uganda - Nampijja, Dorah; Kyoyagala, Stella; Najjingo, Elizabeth; Najjuma, Josephine N; Byamukama, Onesmus; Kyasimire, Lydia; Kabakyenga, Jerome; Kumbakumba, Elias (Public Library of Science, 2024)
A child born in developing countries has a 10 times higher mortality risk compared to one born in developed countries. Uganda still struggles with a high neonatal mortality rate at 27/1000 live births. Majority of these death occur in the community when children are under the sole care of their parents and guardian. Lack of knowledge in new born care, inappropriate new born care practices are some of the contributors to neonatal mortality in Uganda. Little is known about parent/caregivers’ knowledge, practices and what influences these practices while caring for the newborns. We systematically studied and documented newborn care knowledge, practices and associated factors among parents and care givers. To assess new born care knowledge, practices and associated factors among parents and care givers attending MRRH. We carried out a quantitative cross section methods study among caregivers of children from birth to six weeks of life attending a regional referral hospital in south western Uganda. Using pretested structured questionnaires, data was collected about care givers’ new born care knowledge, practices and the associated factors. Data analysis was done using Stata version 17.0. We interviewed 370 caregivers, majority of whom were the biological mothers at 86%. Mean age was 26 years, 14% were unemployed and 74% had monthly earning below the poverty line. Mothers had a high antenatal care attendance of 97.6% and 96.2% of the deliveries were at a health facility Care givers had variant knowledge of essential newborn care with associated incorrect practices. Majority (84.6%) of the respondents reported obliviousness to putting anything in the babies’ eyes at birth, however, breastmilk, water and saliva were reportedly put in the babies’ eyes at birth by some caregivers. Hand washing was not practiced at all in 16.2% of the caregivers before handling the newborn. About 7.4% of the new borns received a bath within 24 hours of delivery and 19% reported use of herbs. Caregivers practiced adequate thermal care 87%. Cord care practices were inappropriate in 36.5%. Only 21% of the respondents reported initiation of breast feeding within 1 hour of birth, Prelacteal feeds were given by 37.6% of the care givers, water being the commonest prelacteal feed followed by cow’s milk at 40.4 and 18.4% respectively. Majority of the respondents had below average knowledge about danger signs in the newborn where 63% and mean score for knowledge about danger signs was 44%. Caretaker’s age and relationship with the newborn were found to have a statistically significant associated to knowledge of danger signs in the newborn baby. There are variable incorrect practices in the essential new born care and low knowledge and awareness of danger signs among caregivers of newborn babies. There is high health center deliveries and antenatal care attendance among the respondents could be used as an opportunity to increase caregiver awareness about the inappropriate practices in essential newborn care and the danger signs in a newborn.
Keywords: Southwestern Uganda; Newborn care knowledge and practices; young infants attending a regional referral hospital